Bioróżnorodność i różne modele niepełnosprawności w kontekście filozofii Michela Foucaulta - Trojanowska, Milena (Understanding Disability: Issues, Research, Reflections, 2021)
Disability is a phenomenon considered from different perspectives. I suggest tracking the history of the perception of disability with an indication of the dominant ways of perceiving this phenomenon at a given period of time. The analysis is conducted with particular emphasis on the attitude developed by Michel Foucault. The knowledge presented by Foucault regarding authority, body, disability and change is treated as a framework to which the emerging models of disability, in particular the medical, functional and social, is written in turn. This review and analysis is intended to lead to a place where the view on the biodiversity as an opportunity to escape from the management, power over disabled bodies. As a result of this work, the final section of the text presents an analysis of the theoretical situation of the lack of power of other members of society over people with disabilities.